PENGARUH KOMPENSASI, PELATIHAN DAN PERAN SUPERVISOR TERHADAP KINERJA PADAKARYAWAN PAGUYUBAN BATIK SI JAMBE, KECAMATAN WONOKERTO, KABUPATEN PEKALONGAN - Wenti Ayu Sunarjo (Fakultas Ekonomi Universitas Pekalongan, 2015)
This research entitle “The Influence of Compensation, Training, and Supervisor Role to The Performance of employees batik club at Sijambe village, Wonokerto, Pekalongan” has the aim to testing corelation amongvariables to reality faced are the poor performance of employees batik club at Sijambe village, Wonokerto,Pekalongan. This research includes the quantitative research, that use the path analysis method. The population is all of ceaftman of batik club at Sijambe village, Wonokerto, Pekalongan Regency. Thesamples amount take with forecasting interval, and use the purposive sampling method to take the samples. The result of this research show thah compensation and training variables have no significanceinfluence to employee performance. But the supervisor role variable has the significance influence to employeeperformance Batik club at Sijambe village, Wonokerto, Pekalongan Regency. Keywords: compensation, training, supervisor role and performance.